2005
DOI: 10.1002/art.21260
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab treatment in patients with primary Sjögren's syndrome: An open‐label phase II study

Abstract: Objective. To investigate the safety and efficacy of B cell depletion treatment of patients with active primary Sjögren's syndrome of short duration (early primary SS) and patients with primary SS and mucosaassociated lymphoid tissue (MALT)-type lymphoma (MALT/primary SS).Methods. Fifteen patients with primary SS were included in this phase II trial. Inclusion criteria for the early primary SS group were B cell hyperactivity (IgG >15 gm/liter), presence of autoantibodies (IgM rheumatoid factor, anti-SSA/SSB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
301
1
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 447 publications
(325 citation statements)
references
References 38 publications
(58 reference statements)
4
301
1
19
Order By: Relevance
“…β2-microglobulin levels show a 'delayed' drop at 16 weeks after treatment [8,12], which was not seen at 6 or 12 weeks after rituximab treatment [8,11]. Serum immunoglobulin free light chains (FLCs) are also affected by rituximab and decrease significantly from week 5 up to week 48 after treatment (unpublished data), in line with findings in RA [19].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…β2-microglobulin levels show a 'delayed' drop at 16 weeks after treatment [8,12], which was not seen at 6 or 12 weeks after rituximab treatment [8,11]. Serum immunoglobulin free light chains (FLCs) are also affected by rituximab and decrease significantly from week 5 up to week 48 after treatment (unpublished data), in line with findings in RA [19].…”
Section: Introductionsupporting
confidence: 66%
“…In other trials, including the TEARS trial, no effect on UWS was observed [6,8,11,15]. Although the mean baseline UWS in the TEARS trial was comparable to the study of Meijer et al, the standard deviation was twice as high, which may influence the power of their analysis.…”
Section: Effects On Exocrine Gland Function and Sicca Symptomsmentioning
confidence: 55%
See 2 more Smart Citations
“…Une telle dissociation est également observée avec l'Acm chimérique anti-CD20 rituximab (➜). Lorsqu'il est administré à des patients atteints de leucémie lymphoïde chronique B, il n'entraîne pas de réponse immune [13,14] ; au contraire 65 % des patients atteints de lupus érythémateux disséminé et 27 % de ceux atteints de polyarthrite rhumatoïde traités par ce même rituximab développent des ADA [15,16]. Quant à l'adalimumab, un anticorps complètement humain, il induit un taux de réponses immunes de 1 à 12 % dans la polyarthrite rhumatoïde [17,18].…”
Section: Facteurs D'immunogénicité Liés Au Produitunclassified